Single cell genotyping of exome sequencing-identified mutations to characterize the clonal composition and evolution of inv(16) AML in a CBL mutated clonal hematopoiesis. (August 2016) - Niemöller, Christoph; Renz, Nathalie; Bleul, Sabine; Blagitko-Dorfs, Nadja; Greil, Christine; Yoshida, Kenichi; Pfeifer, Dietmar; Follo, Marie; Duyster, Justus; Claus, Rainer; Ogawa, Seishi; Lübbert, Michael; et al.
Highlights: Genetics provide insights into evolution of inv(16) AML in CBL mutated hematopoiesis. Single cell genotyping verifies clonal architecture derived from bulk genetic analyses. Mutated PTPRT may contribute to inv(16) AML at later stage by enhancing proliferation. Abstract: We recently described the development of an inv(16) acute myeloid leukemia (AML) in a CBL mutated clonal hematopoiesis. Here, we further characterized the clonal composition and evolution of the AML based on the genetic information from the bulk specimen and analyses of individual bone marrow cells for mutations in CAND1, PTPRT, and DOCK6 . To control for allele dropout, heterozygous polymorphisms located close to the respective mutation loci were assessed in parallel. The clonal composition concluded from exome sequencing suggested a proliferation advantage associated with the acquisition of mutations in CAND1, PTPRT, and DOCK6 . Out of 102 single cell sequencing reactions on these mutations and the respective polymorphisms, analyses yielded conclusive results for at least 2 mutation sites in 12 cells. The single cell genotyping not only confirmed the co-occurrence of the PTPRT, CAND1 and DOCK6 mutations in the same AML clone but also revealed a clonal hierarchy, as the PTPRT mutation was likely acquired after the CAND1 and DOCK6 mutations. This insight had not been possible based solely on the exome sequencing data and suggests that the mutation in PTPRT, which encodes a STAT3-inhibiting protein tyrosine phosphatase, contributed to the AML development at a later stage by enhancing proliferation.